2012
DOI: 10.3928/1081597x-20111122-03
|View full text |Cite
|
Sign up to set email alerts
|

Precision Analysis of Posterior Corneal Topography Measured by Visante Omni: Repeatability, Reproducibility, and Agreement With Orbscan II

Abstract: The Visante Omni provides good repeatability and reproducibility of posterior corneal topography. Overall agreement with the Orbscan II system was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The study found that the device provided highly reproducible intraobserver and interobserver measurements of the posterior corneal curvature (3.0 mm and 6.0 mm, respectively) and of the posterior corneal elevation BFS (5.0 mm and 8.0 mm, respectively). Furthermore, the intraobserver and interobserver mean biases for posterior corneal curvature at 3.0 mm and 6.0 mm did not exceed 0.03 D, 13 and the intraobserver and interobserver mean biases for posterior corneal curvature BFS at 5.0 mm and 8.0 mm did not exceed 0.03 mm. 13 Our findings of high intraobserver and interobserver reproducibility for the above parameters agree with the findings in the previous study.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The study found that the device provided highly reproducible intraobserver and interobserver measurements of the posterior corneal curvature (3.0 mm and 6.0 mm, respectively) and of the posterior corneal elevation BFS (5.0 mm and 8.0 mm, respectively). Furthermore, the intraobserver and interobserver mean biases for posterior corneal curvature at 3.0 mm and 6.0 mm did not exceed 0.03 D, 13 and the intraobserver and interobserver mean biases for posterior corneal curvature BFS at 5.0 mm and 8.0 mm did not exceed 0.03 mm. 13 Our findings of high intraobserver and interobserver reproducibility for the above parameters agree with the findings in the previous study.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the intraobserver and interobserver mean biases for posterior corneal curvature at 3.0 mm and 6.0 mm did not exceed 0.03 D, 13 and the intraobserver and interobserver mean biases for posterior corneal curvature BFS at 5.0 mm and 8.0 mm did not exceed 0.03 mm. 13 Our findings of high intraobserver and interobserver reproducibility for the above parameters agree with the findings in the previous study. However, to our knowledge, no previous study has assessed the intraobserver and interobserver reproducibility of the Visante Omni device's measurements of the corneal parameters of anterior and posterior corneal topography and aberrometry, making our study the first to do so.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The only other study to have investigated the Visante Omni also found good repeatability and reproducibility on humans; interobserver posterior elevation measurements had LoA between À0.08 to 0.08 mm and À0.14 to 0.10 mm for the 8-and 5-mm best-fit spheres, respectively. 22 The imaging capabilities of the Visante Omni enabled us to evaluate the effect of stromal photoablation on the development of ectasia in the rabbit cornea. Deep excimer ablation was performed in order to achieve maximal corneal ectasia.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is used to derive anterior surface topography measurements that are summated with the pachymetric Visante OCT measurements to provide posterior corneal surface topography. We, 21 and others, 22 have previously found that the Visante Omni has excellent repeatability and reproducibility of anterior and posterior corneal topography in healthy patients.…”
Section: Introductionmentioning
confidence: 99%